(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2023)
Background: Klebsiella pneumoniae were considered as normal flora of skin, and intestine. It can cause damage to human lungs; the danger of this bacterium is related to exposure to the hospital surroundings. materials and methods: the detection of Klebsiella pneumoniae on morphological and biochemical tests and then assured with VITEK 2 system. Resistance to antibiotics was determined by Kirby-Baeur method. And genotyping of IMP-1 in isolates was done by PCR technique, then biofilm formation was identified by Micro titer plate method. Results: The present study included a collecting of 50 specimens from different clinical specimens, (blood 40%, urine 30%, sputum 20%, wound infection 10%); 10 isolates were identified as Klebsiella pneumoniae . All isolates, under study, developed high resistance toward Cefitrixon, Ampicillin, Amoxicillin, Ticarcillin, Ticarcillin+Clavulanic acid, and Ceftazidim estimated by disc diffusion method. All isolates characterized by harboring the highest resistant in a percentage reached 100% against antibiotics, under study. This study determined the Minimal Inhibitory Concentration were detected by eight E-test strips for isolates. As well as the isolates were strong biofilm production for three isolates, while three were moderate of biofilm formation and other isolates were weak former; at the value of (P≤0.05) was considered as a significant. Genotype detection of Metalo-beta lactamase (IMP-1) by PCR technique in Klebsiella pneumoniae . Upon using PCR technique exposed only three isolates;30% of isolates (two from urine, one from blood) samples harbored IMP-1 gene. The study was also found relationship between IMP-1 and biofilm formation in isolates which were harboring these genes, when (P ≤ 0.05). Conclusions: K. pneumoniae were isolated from different sources. All isolates were resistant to most antibiotics used in this study. The isolates have Metallo-beta lactamse. PCR was showed K. pneumoniae have IMP-1 gene,.This study also found there was relationship between biofilm formation and IMP-1 gene in K. pneumoniae (P≤0.05).